Predict, Organize, Rehearse, Practice and Evaluate(PORPE) Method to Teach Students’ Reading Comprehension - Afrida Wulansari; Dwi Andriani; Eka Agustina (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
The problem of this study is